2015
DOI: 10.1128/genomea.00214-15
|View full text |Cite
|
Sign up to set email alerts
|

Genome Sequence of EU-Unauthorized Genetically Modified Bacillus subtilis Strain 2014-3557 Overproducing Riboflavin, Isolated from a Vitamin B2 80% Feed Additive

Abstract: This paper announces the genome sequence and annotation of the genetically modified (GM) Bacillus subtilis strain 2014-3557 overproducing riboflavin (vitamin B2). This GM-strain is unauthorized in the European Union. Nevertheless, it has been isolated from a lot of vitamin B2 (riboflavin) 80% feed grade imported to Europe from China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 1 publication
1
31
0
Order By: Relevance
“…The first step in the development of the specific qPCR assay consisted of identifying the junction of the GM-insert into the Bacillus subtilis GM-strains extracted from vitamin B2 samples 2014–3557 [Genbank: JYFL01000000] [ 21 ]. As elaborated in Methods, a BLAST study of the contigs of the previously published sequence of the GM- Bacillus subtilis 2014–3557 isolated from vitamin B2 80 % [Genbank:JYFL01000000.1] [ 21 ] was used to identify the contigs containing the riboflavin biosynthesis operon ribGBAH , with a focus on locating the ribA gene as it has been previously reported that additional expression of this gene encoding the rate limiting enzyme in riboflavin synthesis increases riboflavin synthesis even more as compared to only overexpression of ribGBAH [ 7 , 11 , 24 ]. The overlapping contigs Contig0022 [Genbank:JYFL01000022.1] and Contig0016 [Genbank:JYFL01000016.1] were retrieved as containing genes having 100 % similarity with B. subtilis subsp.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The first step in the development of the specific qPCR assay consisted of identifying the junction of the GM-insert into the Bacillus subtilis GM-strains extracted from vitamin B2 samples 2014–3557 [Genbank: JYFL01000000] [ 21 ]. As elaborated in Methods, a BLAST study of the contigs of the previously published sequence of the GM- Bacillus subtilis 2014–3557 isolated from vitamin B2 80 % [Genbank:JYFL01000000.1] [ 21 ] was used to identify the contigs containing the riboflavin biosynthesis operon ribGBAH , with a focus on locating the ribA gene as it has been previously reported that additional expression of this gene encoding the rate limiting enzyme in riboflavin synthesis increases riboflavin synthesis even more as compared to only overexpression of ribGBAH [ 7 , 11 , 24 ]. The overlapping contigs Contig0022 [Genbank:JYFL01000022.1] and Contig0016 [Genbank:JYFL01000016.1] were retrieved as containing genes having 100 % similarity with B. subtilis subsp.…”
Section: Resultsmentioning
confidence: 99%
“…subtilis str. 168 genes ribH, ribBA, ribE and ribD , involved in riboflavin biosynthesis [ 7 , 25 ], as it could also be deduced from the annotation of the GM- B. subtilis genome sequence [Genbank:JYFL01000000] [ 21 ] (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations